POTENSI PENGGUNAAN MODUL KEANEKARAGAMAN HAYATI DENGAN PENDEKATAN KEARIFAN LOKAL DAN BUDAYA SEBAGAI ALTERNATIF BAHAN AJAR BIOLOGI SMA/MA - Fajar Adinugraha; Adisti Ratnapuri (Jurnal Pro-Life, 2020)
The purpose of this research was to develop a module on biodiversity with a local wisdom and cultural approach according to the Research and Development research method with the Sugiyono R&D stage. This research was conducted in 2 (two) stages, namely the First Stage of Development / Developing the Biodiversity Module with the Local Wisdom and Cultural Approach) and the Second Stage (Testing the use of modules and Mass Production). The Biodiversity Module with the Local Wisdom and Cultural Approach has a score of 91.33, which is in the very valid category. The mean score of knowledge (posttest) in the experimental class was higher than that of the control class, namely the knowledge value of the experimental class ≥65 but there is no significant difference the post-test scores between the control and experimental classes. This is because based on the Mann Whitney U Test, Ucount (54)> Utabel (27) then H0 is accepted. All respondents (100%) gave positive responses to the biodiversity module with the local wisdom and culture approach. Keywords: modules, biodiversity, local wisdom and culture, biology